2021
DOI: 10.1039/d0sm01989e
|View full text |Cite
|
Sign up to set email alerts
|

A structural approach to vibrational properties ranging from crystals to disordered systems

Abstract: Many scientists generally attribute the vibrational anomalies of disordered solids to the structural disorder, which, however, is still under intense debate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…In other words, isostaticity is a critical factor in mechanical marginal stability. 1,2,12,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][75][76][77][78][79][80][81][82][83] Recent simulation results have demonstrated that thermal fluctuations in the marginal states are accompanied by the intermittent rearrangements of particles. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]…”
Section: A Marginal Stability and The Free Energy Landscapementioning
confidence: 99%
See 2 more Smart Citations
“…In other words, isostaticity is a critical factor in mechanical marginal stability. 1,2,12,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][75][76][77][78][79][80][81][82][83] Recent simulation results have demonstrated that thermal fluctuations in the marginal states are accompanied by the intermittent rearrangements of particles. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]…”
Section: A Marginal Stability and The Free Energy Landscapementioning
confidence: 99%
“…For instance, quasi-localized modes coupled to an elastic matrix create soft spots composed of tens to hundreds of particles undergoing displacements. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The low-frequency soft modes exhibit similar behaviors, and the common features of marginal states have been related to the emergence of many local minima in the free-energy landscape. 26,[84][85][86][87] The similarity in anharmonic vibrations suggests that the ensemble of configurations visited by the slow dynamics could reveal the characteristics of marginal stability associated with the free-energy landscape, even though possible configurations depend on a protocol adopted.…”
Section: A Marginal Stability and The Free Energy Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…The isostatic systems can be destabilized by cutting one particle contact unless disordered packings are strictly jammed. In other words, the isostaticity is a critical factor in the mechanical marginal stability [1,2,12,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][75][76][77][78][79][80][81][82][83].…”
Section: A Marginal Stability and The Free Energy Landscapementioning
confidence: 99%
“…Recent simulation results have demonstrated that thermal fluctuations in the marginal states are accompanied by intermittent rearrangements of particles [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. As a consequence, the marginal systems become responsive to have low-frequency soft modes that are nonphononic and anharmonic.…”
Section: A Marginal Stability and The Free Energy Landscapementioning
confidence: 99%